Performance evaluation of a novel monofilar helical antenna with tapered cross-section wire fabricated via metal additive manufacturing - Penchel, Rafael A. [UNESP]; Martins, Nicholas F. [UNESP]; Aldaya, Ivan [UNESP]; de Oliveira, José A. [UNESP]; dos Santos, Mirian P. [UNESP]; Jardini, Andre L.; Avila, Julian [UNESP]; Rosa, Guilherme S. (Elsevier, 2024)
This paper presents a novel formulation for a generalized helical antenna that incorporates non-uniform helix diameters, non-uniform helix spacing, and non-uniform wire cross-section, providing additional degrees of freedom for optimization. By carefully defining the transition between the helix and the center feed point, a thicker wire was used at the base to enhance the antenna's operating bandwidth capability and mechanical strength, eliminating the need for additional support structures. The fabrication process utilized metal additive manufacturing (MAM) with Maraging steel. The results demonstrate that the helical antenna with a tapered cross-section wire (with a thicker base and a thinner tip) exhibits significantly better performance compared to the control models for operation in the X-band. This design amalgamates impedance matching from antennas with uniform thick wires and radiation characteristics from antennas with uniform thin wires. The major contribution of this work is the demonstration that employing tapered wire cross-sections can enhance helical antenna performance, thereby introducing a new design parameter in metal additive manufacturing. Specifically, we present an eight-turn helical antenna that achieved a measured reflection coefficient less than −10 dB and axial ratio less than 1 dB over the X band, with a peak realized gain in RHCP of 10.8 dBic.
Keywords: Additive manufacturing; Axial mode; Helical antenna; Non-uniform pitch angle